Genomic analysis of Rad26 and Rad1–Rad10 reveals differences in their dependence on Mediator and RNA polymerase II - Gopaul, Diyavarshini; Denby Wilkes, Cyril; Goldar, Arach; Giordanengo Aiach, Nathalie; Barrault, Marie-Bénédicte; Novikova, Elizaveta; Soutourina, Julie

(untitled) (Genome Research, 2022)
Mediator is a conserved coregulator playing a key role in RNA polymerase (Pol) II transcription. Mediator also links transcription and nucleotide excision repair (NER) via a direct contact with Rad2/ERCC5(XPG) endonuclease. In this work, we analyzed the genome-wide distribution of Rad26/ERCC6(CSB) and Rad1–Rad10/ERCC4(XPF)-ERCC1, addressing the question of a potential link of these proteins with Mediator and Pol II in yeast Saccharomyces cerevisiae. Our genomic analyses reveal that Rad1–Rad10 and Rad26 are present on the yeast genome in the absence of genotoxic stress, especially at highly transcribed regions, with Rad26 binding strongly correlating with that of Pol II. Moreover, we show that Rad1–Rad10 and Rad26 colocalize with Mediator at intergenic regions and physically interact with this complex. Using kin28 TFIIH mutant, we found that Mediator stabilization on core promoters leads to an increase in Rad1–Rad10 chromatin binding, whereas Rad26 occupancy follows mainly a decrease in Pol II transcription. Combined with multivariate analyses, our results show the relationships between Rad1–Rad10, Rad26, Mediator, and Pol II, modulated by the changes in binding dynamics of Mediator and Pol II transcription. In conclusion, we extend the Mediator link to Rad1–Rad10 and Rad26 NER proteins and reveal important differences in their dependence on Mediator and Pol II. Rad2 is the most dependent on Mediator, followed by Rad1–Rad10, whereas Rad26 is the most closely related to Pol II. Our work thus contributes to new concepts of the functional interplay between transcription and DNA repair machineries, which are relevant for human diseases including cancer and XP/CS syndromes.